Metallurgical Investigation of HSLA Steel Subjected to Underwater Explosion - V. Bhujanga Rao; R. Rajendran; A.V. Jaykumar; K.H.B.S. Satyanarayana (Shock and Vibration, 1994)
The metallurgical behaviour of HSLA steel subjected to underwater explosion is of prime importance because of its structural applications in underwater vehicles. HSLA steel plates 300 × 250 × 4 mm were subjected to single and repetitive shock loadings and the point of rupture was identified. Test plates exhibited mode-I (large ductile deformation) and mode-II (tensile tearing) macroscopic failures. Electron micrographic and fractographic examination showed that the initiation of fracture was due to adiabatic shearing and the microscopic mode of failure was ductile. Plates subjected to single shock showed an increase in residual hardness and at the point of rupture it was approximately one-third higher than the initial residual hardness.